ANALISIS HUBUNGAN SELF-REGULATED LEARNING TERHADAP KEMAMPUAN BERPIKIR REFLEKTIF MATEMATIS SISWA SMP SYSTEMATIC LITERATURE REVIEW - Anisa Anisa; Heni Pujiastuti; Hepsi Nindiasari (De Fermat : Jurnal Pendidikan Matematika, 2026)
Mathematical reflective thinking ability is a higher-order skill vital in mathematics education. Yet, research on its link with self-regulated learning (SRL) among junior high school students is limited and unsystematically reviewed. This study examines the relationship between SRL and mathematical reflective thinking ability through a 10-year (2016–2026) systematic literature review, identifying patterns and implications for mathematics education at the junior high school level. Using Systematic Literature Review (SLR) per PRISMA guidelines, searches on Google Scholar, ERIC, and accredited national journals employed keywords: "self-regulated learning," "mathematical reflective thinking ability," and "junior high school students." Of 30 articles identified, 15 met the inclusion criteria and were analyzed using descriptive qualitative methods. Findings show a consistent positive correlation between SRL and mathematical reflective thinking ability. High-SRL students more comprehensively fulfill reflective thinking indicators (reacting, elaborating, contemplating) compared to medium/low-SRL peers. This relationship is mediated by the structural alignment between SRL phases (forethought, performance control, self-reflection) and the cognitive processes underlying reflective thinking. Problem-Based Learning (PBL) consistently optimizes the role of SRL in developing mathematical reflective thinking ability. The study strengthens the empirical basis for fostering SRL in junior high school mathematics learning and urges the integration of metacognitive strategies into the curriculum